GAMIFICATION AS A PEDAGOGIC TOOL IN MATHEMATICS TEACHING AND LEARNING - Ediane de Fátima Jacques; Luis Fernando Lopes; Tania Clemente da Silva (Revista Interinstitucional Artes de Educar, 2023)
This bibliographical study, presented in the form of an experience report, addresses the use of gamification and games as a pedagogical tool to collaborate in the teaching of Mathematics in the final years of Elementary School. The objective was to analyze the use of technologies, especially digital ones, as a pedagogical resource, with a view to collaborating with the development of students' reasoning, contributing to the construction of knowledge in a creative way. To this end, the activities were developed on the Wordwall and Kahoot websites for classes in the Final Years of Elementary School. It is understood that these activities can be used in a disciplinary, interdisciplinary, and transdisciplinary way, as well as being carried out individually or in groups, with autonomy, protagonism, involvement, creativity, and planning. The results indicate that activities with gamification and games, when carefully planned, favor the narrowing of the real world with the virtual world and can be an alternative tool in the student's development process to collaborate with the teacher in teaching Mathematics as a pedagogical strategy.